Stochastic methods in neuroscience - Laing, Carlo; Lord, Gabriel J. (Oxford : Oxford University Press, 2010)
This text concentrates on the intersection between stochastic dynamics and neuroscience, presenting a series of self-contained chapters on major aspects of noise and neuroscience, each written by an expert in their particular field.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Computational neuroscience; Stochastic processes; Neurosciences -- Mathematics